(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
T.S. Eliot was the most towering and dominating man ofletters of the twentieth century. He was a versatile genius who during his longspan of productive activity achieved distinction as a poet, playwright, andcritic. T.S. Eliot’s art of crystallizing his thought in striking phrases hasgained for him wide popularity and appeal. Phrases like "Dissociation ofSensibility," "Objective Correlative", and "Unification ofSensibility" have gained wide currency. T.S. Eliot formulated his theoriesof poetry. The present article investigates the development of Eliot’s theoryof poetry as a master craftsman, who left on them the stamp of his profoundcritical sense.